2019
DOI: 10.1016/j.pnpbp.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression changes related to immune processes associate with cognitive endophenotypes of schizophrenia

Abstract: Schizophrenia is a heterogeneous disorder characterized by a spectrum of symptoms and many different underlying causes. Thus, instead of using the broad diagnosis, intermediate phenotypes can be used to possibly decrease the underlying complexity of the disorder. Alongside the classical symptoms of delusions and hallucinations, cognitive deficits are a core feature of schizophrenia. To increase our understanding of the biological processes related to these cognitive deficits, we performed a genome-wide gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Most of the endophenotypes were normally distributed, however the Trail Making and Stroop tasks were transformed so that the scores represented speed (number of items/performance time). As the neuropsychological endophenotypes are related, they could be grouped into five first-order factors using factor analysis (Table2), and a second-order general ability factor (g-factor) based upon previous results (45) for cognition related traits. The factor analysis was performed with Mplus 7.3.…”
Section: Endophenotypes and Qtdtmentioning
confidence: 99%
“…Most of the endophenotypes were normally distributed, however the Trail Making and Stroop tasks were transformed so that the scores represented speed (number of items/performance time). As the neuropsychological endophenotypes are related, they could be grouped into five first-order factors using factor analysis (Table2), and a second-order general ability factor (g-factor) based upon previous results (45) for cognition related traits. The factor analysis was performed with Mplus 7.3.…”
Section: Endophenotypes and Qtdtmentioning
confidence: 99%
“…These genes may uncover novel pathways underlying some behavioral trait contributing to disease etiology. For example, it was recently shown that expression of genes associated with immunological processes vary with cognitive performance in familial schizophrenia 21 . So, our method to identify repurposable drugs may be tested on schizophrenia, in which differential gene expression plays a critical role.…”
Section: Introductionmentioning
confidence: 99%
“…Many common genetic variants and rare functional mutations make up the polygenic architecture of SCZ (Henriksen et al, 2017). In SCZ, common and rare genetic variants are associated with disorders of -Vuoti et al, 2019;Boyajyan et al, 2015;Jiang et al, 2020). In this study, we focused on rare functional mutations with minor allele frequency (MAF) < 0.01 in the candidate gene, TENM4.…”
Section: Discussionmentioning
confidence: 99%